A New Strategy for Calixindole Formation: Synthesis of a Calix[3]indole with 2,2; 7,2; 7,7-Methylene Linkages and a New Calix[4]indole with 2,2; 7,2; 7,7; 2,7-Methylene Linkages - Somphol, Kittiya; Chen, Rui; Bhadbhade, Mohan; Kumar, Naresh; Black, David StC. (Synlett, 2013)
A new strategy of acid-catalysed reactions of indole methanols with a 3-aryl-4,6-dimethoxyindole-7-aldehyde leads to an efficient synthesis of a calix[3]indole with 2,2; 7,2; 7,7-links. A new calix[4]indole containing four indole units with 2,2; 7,2; 7,7; 2,7-links has also been prepared by this strategy.
Keywords: indoles; diindolylmethanes; macrocyclic compounds; acid-catalysed reactions; ipso-substitution reactions; formaldehyde extrusion